2017
DOI: 10.1093/mnras/stx2933
|View full text |Cite
|
Sign up to set email alerts
|

Merging black hole binaries: the effects of progenitor's metallicity, mass-loss rate and Eddington factor

Abstract: The first four gravitational wave events detected by LIGO were all interpreted as merging black hole binaries (BHBs), opening a new perspective on the study of such systems. Here we use our new population-synthesis code MOBSE, an upgraded version of BSE (Hurley et al. 2002), to investigate the demography of merging BHBs. MOBSE includes metallicity-dependent prescriptions for mass loss of massive hot stars. It also accounts for the impact of the electron-scattering Eddington factor on mass loss. We perform > 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
267
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 302 publications
(281 citation statements)
references
References 96 publications
(170 reference statements)
10
267
2
2
Order By: Relevance
“…A number of formation channels for binary black hole mergers have previously been suggested in the literature, including isolated binaries of massive stars that evolve through a common envelope phase [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], or through a phase of chemically homogeneous evolution [38][39][40], few-body interactions at the core of dense stellar environments, such as old globular clusters [41][42][43][44][45][46][47][48][49], young open clusters [50][51][52][53], or nuclear clusters at the center of galaxies [54,55]. It has also been suggested that binaries are driven toward merger by nearby supermassive black holes [56], their accretion disks [57][58][59], or by tertiary stellar companions [60][61][62][63].…”
Section: Possible Formation Channelsmentioning
confidence: 99%
“…A number of formation channels for binary black hole mergers have previously been suggested in the literature, including isolated binaries of massive stars that evolve through a common envelope phase [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], or through a phase of chemically homogeneous evolution [38][39][40], few-body interactions at the core of dense stellar environments, such as old globular clusters [41][42][43][44][45][46][47][48][49], young open clusters [50][51][52][53], or nuclear clusters at the center of galaxies [54,55]. It has also been suggested that binaries are driven toward merger by nearby supermassive black holes [56], their accretion disks [57][58][59], or by tertiary stellar companions [60][61][62][63].…”
Section: Possible Formation Channelsmentioning
confidence: 99%
“…We use simulations performed with the populationsynthesis code MOBSE [16]. MOBSE is an upgrade of the arXiv:1906.04197v1 [gr-qc] 10 Jun 2019 Among the many physical processes involved in the formation of compact binaries that can merge within a Hubble time, the so called common-envelope phase is believed to be critical [19,20].…”
Section: Astrophysical Populationsmentioning
confidence: 99%
“…In Sec. II we present our astrophysical populations based on the MOBSE population-synthesis code [15,16]. In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other groups published their results on DCO local merger rates during the last year. The highest NS-NS R loc of ∼600 Gpc −3 yr −1 quoted by Mapelli & Giacobbo (2018) (dashed green line in Fig. 1) was obtained assuming 5 times higher efficiency of CE ejection than in their reference model and additionally requiring that all NS form with low natal kicks (drawn from Maxwellian distribution with velocity dispersion σ=15 km/s).…”
Section: Binary Evolution and Dns Merger Ratesmentioning
confidence: 89%